1961
DOI: 10.1136/oem.18.2.120
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bacterial Endotoxins in Occupational Diseases Caused by Inhaling Vegetable Dusts

Abstract: A large group of occupational diseases connected with the inhalation of various vegetable dusts, especially in the textile industry, have certain main symptoms in common such as fever, coughing, dyspnoea, and general malaise. In most cases the symptoms are more prominent on Mondays or on resuming work after one or more days of interruption. The symptomatology of these diseases and the Monday effect leads to the hypothesis that they are due to the inhalation of the endotoxins of gram-negative bacteria that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 14 publications
3
40
0
Order By: Relevance
“…World War II prevented further development of the 'endotoxin hypothesis' which was then forgotten for many years. About 20 years later the hypothesis was revived by the Italian scientists Pernis et al [21] and Cavagna et al [22] who demonstrated by well-designed experiments the role of bacterial endotoxin in causing diseases due to exposure to cotton dust; however, without attributing this hypothesis to any species of Gram-negative bacteria. Cavagna [23], using biological tests in the skin of rabbits, quantified for the first time the 'endotoxin-like substances' in settled and airborne cotton dust.…”
Section: Dust-borne Endotoxins and Allergens Of Pantoea Agglomerans -mentioning
confidence: 99%
“…World War II prevented further development of the 'endotoxin hypothesis' which was then forgotten for many years. About 20 years later the hypothesis was revived by the Italian scientists Pernis et al [21] and Cavagna et al [22] who demonstrated by well-designed experiments the role of bacterial endotoxin in causing diseases due to exposure to cotton dust; however, without attributing this hypothesis to any species of Gram-negative bacteria. Cavagna [23], using biological tests in the skin of rabbits, quantified for the first time the 'endotoxin-like substances' in settled and airborne cotton dust.…”
Section: Dust-borne Endotoxins and Allergens Of Pantoea Agglomerans -mentioning
confidence: 99%
“…Important work was done by Cavagna et al [1969] and Pernis et al [1961], but not until Cinkotai et al [ 19771 published their findings from an investigation in Lancashire cotton mills could a dose-response relationship be established between the number of airborne Gram-negative bacteria and the prevalence of one of the symptoms after cotton dusts exposure-subjective chest tightness-among workers in cotton mills.…”
Section: Bacterial Endotoxin Historical Backgroundmentioning
confidence: 99%
“…Questioning a random sample of byssinotics who attend Manchester Pneumoconiosis Medical Panel revealed that 26% had suffered from mill fever on first starting work, but the prevalence could well have been higher because some of those questioned were elderly and could not remember what happened to them when they started work at age 12 to 14. The symptoms of mill fever could be the result of a reaction to endotoxin contaminating the dust [30]. It seems in our experience rarely to occur now.…”
Section: Other Diseases and Conditionsmentioning
confidence: 94%